Relationship between research process factors and research project performance among Malaysian undergraduates in Chinese studies - Yee, Sow Kee (2015)
This study investigated the factors influencing the research process and performance of the final year research projects based on the perceptions of the graduates of Chinese studies in four selected universities in Malaysia. The aims of this study are: 1. to identify the research process factors used in the final research project, 2. to analyze the relationships between research process factors and the performance of the final year research projects obtained by the undergraduates of Chinese study from Universiti Putra Malaysia, and 3. to identify the factors influencing the research process factors towards the performance of the final year research projects obtained by undergraduates of Chinese study from Universiti Putra Malaysia. Quantitative research methodology was adopted in this study to collect research data. The conceptualization of literacy was used to set the measurement of scales for the questionnaires. This study had two sets of questionnaires which became the instrument of this study to collect feedback from the graduates on the information related to the research projects. The instument was found to be reliable to be used for factor analysis. The outcomes from the factors analysis indicate that there are six main factors influencing the research process and performance of their final year research projects. Ranking of the factors was done by using the independent T-test: First, collection of research materials; second, format of the research writing; third, satisfaction with the research project; fourth, difficulties and problems in collecting research materials;fifth, research methodology and sixth, project supervisors. The fourth factor had a siginificant relationship with the scores of the final year research projects especially for the respondents who did not obtain “very good” results for their research projects. Pearson’s correlation analysis showed that only three factors had correlations with the scores of the final year research projects produced by the respondents, which were the third, forth and sixth factors. This study can provide useful information to help the undergraduates in Chinese study to gain better understanding on the process of conducting the final year research projects. The research outcomes of this study also can provide information to them in relation to the factors affecting the research process and performance of the final year research projects. Furthermore, the findings of this study can persuade present and future undergraduates to have positive attitude to interact and collaborate with their project supervisors in order to produce high quality research projects.